Kontroversi Kewafatan dan Kedatangan Nabi Isa pada Akhir Zaman (Perspektif Teologis) - Syarifatun Nafsih (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2021)
The story of the Prophet 'Isa as is a complete story in the Qur'an. Especially regarding his death and arrival to the world at the end of the age which is full of question marks. Some argue that the death that occurred to the Prophet 'Isa was death in general, crucified,rised in sleep, and some others argue that his body and spirit were raised by Allah (alive). Likewise, regarding his arrival at the end of time, some argue that he really appears as a sign of the coming of the apocalypse, but others state that it is not a certainty that he will reappear, because the Prophet Muhammad has been crowned as the seal of the Prophets and Apostles. Using descriptive-analytical method, this research will try to explain the theological view regarding the death and resurrection of Prophet ‘Isa as at the end of time. The results of the study indicate that there are this controversy is not only between beliefs, but among Muslims themselves, it is alleged that there are various interpretations of the verses related to the death of the Prophet 'Isa as